Switching Overvoltages Protection of Power Electronics Converters with Gate Turn-off Thyristors - Yevhen Fediv; Olha Sivakova; Vladyslav Lysiak; Mykhailo Korchak (Energy Engineering and Control Systems)
Using the developed models in the “Simulink” visual programming environment of the “Matlab” application package using the “SimPowerSystem” and “Simscape Electrical” libraries, a comparative analysis of methods and techniques for limiting switching overvoltages in power converters, which are controlled by unlocking two-operation thyristors, was performed. The choice of a specific means of limitation is individual for each converter and depends on many factors - the power of the converter, the current-voltage characteristics of thyristors, the parameters of the power supply, and so on. Studies have shown that the most effective protection against voltage pulses with short duration and significant amplitude is the use of “Transient Voltage Suppressors” limiting diodes, the action of which is based on the use of avalanche breakdown during the time of thyristor unlocking.